Corrigendum to "Binder-free nanostructured germanium anode for high resilience lithium-ion battery". (20th August 2022) - Fugattini, S.; Gulzar, U.; Andreoli, A.; Carbone, L.; Boschetti, M.; Bernardoni, P.; Gjestila, M.; Mangherini, G.; Camattari, R.; Li, T.; Monaco, S.; Ricci, M.; et al.
Graphical Abstract: Image, graphical abstract